Preparation method and application of lithium defect type layered spinel composite phase lithium-rich manganese-based positive electrode material
Preparation of lithium-defective layered spinel composite phase lithium-manganese-based positive electrode material through high-temperature thermal shock method, solving the attenuation problem of lithium-defective materials, achieving high-efficiency lithium-ion transmission and long-cycle performance, and reducing the lithium source Cost and process complexity.
Patent Information
- Application Number
- CN202411615230.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-13
Smart Images

Figure CN119230797A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode material preparation, and in particular to a preparation method and application of a lithium-defective layered spinel composite phase lithium-rich manganese-based positive electrode material. Background Art
[0002] The development of high-performance lithium battery technology is crucial for the advancement of a variety of applications ranging from consumer electronics to electric vehicles. To achieve this goal, lithium-ion battery cathode materials must be further improved to achieve longer service life, lower production costs, better safety and environmental protection. −1 ), Cobalt-free lithium-rich manganese-based layered transition metal (TM) oxides, as a promising class of cathode materials, are highly competitive among current commercial cathode materials and have attracted widespread attention. In the crystal structure, lithium-rich manganese-based layered oxides can be considered as ordered rock salt derivatives (LiTMO2, R3-m), in which octahedrally coordinated TM and Li cations preferably form alternating layers connected by interlayer oxygen, supplemented by a superlattice (Li2MnO3, C2 / m) formed by Li replacing 1 / 3 of the TM cations in the TM layer. The unique structure allows anions (O 2− →(O2) n− , 1≤n<3) redox process occurs in the lithium-rich manganese-based cathode, which is the reason for the high capacity. However, the anion redox reaction inevitably leads to a certain degree of oxygen release, which is the direct cause of the voltage decay of lithium-rich manganese-based cathode materials. At the same time, low first coulombic efficiency, severe voltage hysteresis, slow kinetics, and irreversible structural phase change are the main problems that plague the current generation of lithium-rich manganese-based cathode materials.
[0003] The modification measures for the low first-cycle coulombic efficiency, poor cycle and rate performance of cobalt-free lithium-rich manganese-based positive electrode materials include element doping, surface coating, morphology control and crystal plane regulation. Adjusting the grain boundary structure to optimize the performance of the material is a classic solution in materials science. For example, CN 117637994A discloses a lithium-defect lithium-rich manganese-based positive electrode material and its preparation method and application. The preparation method of a lithium-defect lithium-rich manganese-based positive electrode material in the embodiment comprises the following steps: (1) mixing a lithium-rich manganese-based precursor and lithium hydroxide, and then placing the mixture in a muffle furnace and calcining it at 900°C for 12 hours to obtain a positive electrode material with lithium defects (chemical formula Li 1.12 Ni 0.2 Mn 0.6 O2); the molar ratio of lithium ions in the lithium hydroxide to the total metal ions in the lithium-rich manganese-based precursor is 1.4, and the lithium-rich manganese-based precursor is Ni 0.2 Mn 0.8(OH)2; (2) placing the positive electrode material with lithium defects described in step (1) in an ALD reactor, introducing a coating source gas for 10s under a nitrogen atmosphere, a heating stage temperature of 120°C, a reactor hot well temperature of 450°C, and a purge temperature of 100°C, to coat aluminum oxide on the positive electrode material with lithium defects described in step (1) to obtain the lithium-defective lithium-rich manganese-based positive electrode material, wherein the coating source gas is trimethylaluminum. The lithium-defective lithium-rich manganese-based positive electrode material prepared by this method through coupling surface coating and grain boundary coating with lithium-defect technology has high rate performance and excellent long-term cycle stability, and can also suppress voltage decay to a certain extent. However, the optimal lithium deficiency of the prepared lithium-defective positive electrode material is only within 7%, and the positive electrode material formed by calcination has no special structure. However, excessive (>10%) lithium defects are usually counterproductive (L Huang et al., Advanced Energy Materials, 2023, 13(4): 2202345.). The presence of a large number of lithium vacancies and the slow insertion of lithium ions after long-term calcination will lead to phase separation between the Li-rich phase and the Mn-rich phase, thereby causing the performance of the positive electrode material to decay. Summary of the invention
[0004] In order to overcome the shortcoming that the traditional method cannot prepare more lithium-deficient positive electrode materials, the present invention provides a preparation method and application of a lithium-deficient layered spinel composite phase lithium-rich manganese-based positive electrode material.
[0005] The preparation method of the present invention is based on Ni x Mn 1-x CO3 and lithium salts are used as raw materials, and the characteristics of rapid temperature rise and fall and short-term heat preservation in high-temperature thermal shock technology are used to achieve the preparation of lithium-rich manganese-based positive electrode materials with a large number of lithium defects (lithium deficiency of up to 20%). At the same time, the presence of a large number of lithium vacancies in situ induces the formation of a layered spinel composite structure, which makes the positive electrode material have high initial efficiency and excellent long-cycle stability. This method has simple process steps, greatly reduces the amount of lithium, saves lithium source costs, and is conducive to large-scale production.
[0006] Specifically, the purpose of the present invention is achieved by the following technical solution: a preparation method of a lithium-rich manganese-based positive electrode material synthesized by a rapid thermal shock method with a "lithium-defective" layered spinel composite phase, the preparation method comprising the following steps: (1) Ni x Mn 1-x CO3 and lithium salt are mixed; the molar ratio of lithium ions in the lithium salt to total metal ions in the precursor is less than 1.5; 0.2≤x<1; the lithium salt includes but is not limited to lithium carbonate and / or lithium hydroxide.
[0007] (2) The powders uniformly mixed in step (1) are spread on a heated substrate, and the heated substrate is powered in an air atmosphere to perform a thermal shock treatment on the powders, the temperature is 800-1000°C, and the holding time is 20-60s, to obtain the lithium-deficient lithium-rich manganese-based positive electrode material. The thermal shock temperature is preferably 900°C, and the holding time is preferably 20s. In the heating and cooling program, the heating and cooling rate is 100°C / s-500°C / s.
[0008] The present invention can generate lithium vacancies during the sintering process by reducing the amount of lithium, inducing the generation of spinel structure. The three-dimensional lithium ion diffusion channel of the spinel phase is conducive to accelerating the lithium ion transmission speed and improving the rate performance; at the same time, it can alleviate the irreversible phase change of the lithium-rich manganese-based positive electrode material during the cycle process, and reduce the capacity and voltage decay; the lithium deficiency of the lithium-deficient lithium-rich manganese-based positive electrode material formed by calcination in a traditional tubular furnace is 7%, not more than 10%. However, a mixture with a smaller amount of lithium (lithium deficiency greater than 10%) will cause phase separation between the Li-rich phase and the Mn-rich phase due to the slow lithium ion embedding and lithium volatilization phenomenon under long-term calcination in a tubular furnace, thereby causing the attenuation of the performance of the positive electrode material.
[0009] The present invention targets lithium-deficient lithium-rich manganese-based positive electrode materials, and realizes rapid embedding of lithium ions into the precursor lattice by extremely rapid heating in a high-temperature thermal shock method. The short insulation time suppresses the volatilization of lithium elements and the phase separation of Li-rich phase and Mn-rich phase. After rapid cooling, a layered spinel lithium-rich manganese-based positive electrode material with uniform composition and greater lithium deficiency is formed, thereby improving the first-cycle coulomb efficiency and long-cycle performance of the lithium-rich manganese-based positive electrode material.
[0010] In certain embodiments of the present invention, the molar ratio of lithium ions in the lithium salt to the total metal ions in the lithium-rich manganese-based precursor is 1.1-1.4. More preferably, it is 1.2;
[0011] The heating substrate used in the present invention generates heat when powered on and may be carbon cloth, graphite paper, or metal foil.
[0012] The Ni x Mn 1-x CO3 can be obtained by conventional co-precipitation method.
[0013] The present invention also relates to the use of the lithium-deficient layered spinel composite phase lithium-rich manganese-based positive electrode material prepared by the above method as a positive electrode material for a lithium battery.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The beneficial result of the present invention is to provide a lithium-deficient lithium-rich manganese-based positive electrode material with a larger lithium deficiency prepared by a high-temperature thermal shock method, and its unique layered spinel composite structure has a high first efficiency and excellent long-cycle performance. The ultra-fast heating and cooling rate allows the lithium ions in the calcination process to be quickly embedded in the bulk phase of the material, and the short insulation time inhibits the volatilization of the lithium source and the separation of the Li-rich phase and the Mn-rich phase, so as to prepare a lithium-rich manganese-based positive electrode material with uniform composition, solve the phase separation phenomenon caused by excessive lithium deficiency in the slow and long-term synthesis process of the traditional tubular furnace, and realize the preparation of high-performance layered spinel composite structure lithium-rich manganese-based positive electrode materials in such a high lithium deficiency environment. The 0.1C first discharge specific capacity of the lithium-deficient lithium-rich manganese-based positive electrode material prepared by this method reaches 282 mAh / g, the first efficiency reaches 94%, and the capacity retention rate of 100 cycles of half-battery cycles at 2.0-4.8V and 1C is 91%, and the capacity retention rate of 200 cycles is 80%. This shows that the material of the present invention has excellent electrochemical properties as a positive electrode material for lithium-ion batteries.
[0015] The present invention provides a method for preparing a lithium-rich manganese-based positive electrode material with a lithium-deficient layered spinel composite structure. The method greatly reduces the amount of lithium to a great extent, saves the cost of lithium source, has simple process steps, and is expected to achieve large-scale promotion and production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is the temperature-time variation curve of high temperature thermal shock during the calcination process of the present invention; Figure 2 It is a lithium-deficient layered spinel composite structure lithium-rich manganese-based positive electrode material Li prepared by high-temperature thermal shock method. 0.96 Ni 0.2 Mn 0.6 XRD pattern of O2; Figure 3 Lithium-defective layered spinel composite structure lithium-rich manganese-based cathode material Li prepared by high temperature thermal shock method 0.96 Ni 0.2 Mn 0.6 High-resolution transmission electron microscopy (HRTEM) of O2.
[0017] Figure 4 Layered spinel composite structure lithium-rich manganese-based cathode materials Li with different lithium deficiency prepared by high temperature thermal shock method x Ni 0.2 Mn 0.6 The first cycle charge and discharge curve of the O2 sample as electrode material at a current density of 0.1C; Figure 5 Layered spinel composite structure lithium-rich manganese-based cathode materials Li with different lithium deficiency prepared by high temperature thermal shock method x Ni 0.2 Mn0.6 Cyclic performance curve of O2 sample as electrode material at 1C current density; Figure 6 Lithium-rich manganese-based cathode materials with different lithium deficiencies prepared in a traditional tube furnace x Ni 0.2 Mn 0.6 The first cycle charge and discharge curve of the O2 sample as electrode material at a current density of 0.1C; Figure 7 Lithium-defective layered spinel composite structure lithium-rich manganese-based cathode material Li prepared by sol-gel method combined with high temperature thermal shock method 0.96 Ni 0.2 Mn 0.6 XRD pattern of O2; Figure 8 Lithium-defect layered spinel composite structure lithium-rich manganese-based cathode material Li prepared by sol-gel method combined with high temperature thermal shock method 0.96 Ni 0.2 Mn 0.6 The first cycle charge and discharge curve of the O2 sample as electrode material at a current density of 0.1C. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further illustrated by specific embodiments below.
[0019] The technical solutions and advantages of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0020] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0021] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0022] In the following examples, Ni 1 / 4 Mn 3 / 4 CO3 is used as a sample to illustrate the present invention so that those skilled in the art can fully understand the implementation scheme and technical effects of the present invention. Those skilled in the art should understand that other Ni x Mn 1-x CO3 is also applicable to the present invention. 1 / 4 Mn 3 / 4 CO3 is only for the purpose of describing specific embodiments and is not intended to limit the present application.
[0023] Example 1 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-defective" layered spinel composite phase using a rapid thermal shock method, the preparation method comprising the following steps: (1) Synthesis of Ni by coprecipitation method 1 / 4 Mn 3 / 4 CO3, the specific method is: nickel sulfate and manganese sulfate are mixed according to n(Ni):n(Mn)=1:3, and the total metal ion concentration of 5.0L is 1.8mol·L -1 The total concentration of sodium carbonate was 2 mol·L -1 Aqueous solution was prepared with 7.0L of ammonia water with a molar concentration of 1.5 mol·L -1 Then, the mixed salt solution, sodium carbonate solution and ammonia solution were added dropwise to the coprecipitation reactor and stirred continuously at a dropping rate of 1 mL min -1 The reactor temperature was controlled at 55°C, the stirring speed was 1100 rpm, the pH was 10.9, and the complexing agent concentration was 0.55 mol·L -1 After 48 hours of coprecipitation reaction, the lithium-rich manganese-based carbonate precursor Ni 1 / 4 Mn 3 / 4 CO3; (2) The lithium-rich manganese-based cathode precursor Ni 1 / 4 Mn 3 / 4 CO3 and lithium carbonate are uniformly mixed; the molar ratio of lithium ions in the lithium carbonate to the total metal ions in the precursor is 1.2; (3) Spread the powder evenly mixed in step (2) on a carbon cloth and calcine in air, with a current of 45A and a target temperature of 900°C. After reaching the target temperature, keep it for 20 seconds. In the air environment, the heating and cooling speed is about 400°C / s, and finally calcination forms a lithium-rich manganese-based positive electrode material Li 0.96 Ni 0.2 Mn 0.6 O2.
[0024] Figure 1 It is the temperature-time variation curve of the material after high temperature thermal shock process; Figure 2 Lithium-defective layered spinel composite structure lithium-rich manganese-based cathode material Li prepared by high temperature thermal shock method 0.96 Ni 0.2 Mn 0.6The XRD spectrum of O2 shows that its diffraction peaks match those of R-3m, and the diffraction peaks at 22-25° are attributed to the superlattice structure of the C2 / m phase. The diffraction peaks of all materials are relatively sharp, and the split peaks of (006) / (102) and (018) / (110) are also very obvious, with good layered and crystallinity. Due to the low content of spinel inside, XRD cannot detect it, but from Figure 3 High-resolution transmission electron microscopy can find that its diffraction spots can match the layered structure ( 0)( 11), (001) plane and (220) plane of spinel phase, which also proves that the layered spinel composite structure is synthesized by a large number of lithium defects.
[0025] Example 2 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-defective" layered spinel composite phase using a rapid thermal shock method, the preparation method comprising the following steps: (1) The lithium-rich manganese-based cathode precursor Ni 1 / 4 Mn 3 / 4 CO3 and lithium carbonate are uniformly mixed; the molar ratio of lithium ions in the lithium carbonate to the total metal ions in the precursor is 1.1; (2) The powders evenly mixed in step (1) are spread on a carbon cloth and calcined in air. The current is 45A and the target temperature is 900°C. After reaching the target temperature, the temperature is maintained for 20 seconds. In the air environment, the heating and cooling speed is about 400°C / s. Finally, the lithium-rich manganese-based positive electrode material Li is calcined. 0.88 Ni 0.2 Mn 0.6 O2.
[0026] Example 3 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-defective" layered spinel composite phase using a rapid thermal shock method, the preparation method comprising the following steps: (1) The lithium-rich manganese-based cathode precursor Ni 1 / 4 Mn 3 / 4 CO3 and lithium carbonate are uniformly mixed; the molar ratio of lithium ions in the lithium carbonate to the total metal ions in the precursor is 1.2; (2) The powders evenly mixed in step (1) are spread on a carbon cloth and calcined in air. The current is 40A and the target temperature is 850°C. After reaching the target temperature, the temperature is maintained for 20 seconds. In the air environment, the heating and cooling speed is about 400°C / s. Finally, the lithium-rich manganese-based positive electrode material Li 0.96 Ni 0.2 Mn 0.6 O2.
[0027] Example 4 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-defective" layered spinel composite phase using a rapid thermal shock method, the preparation method comprising the following steps: (1) The lithium-rich manganese-based cathode precursor Ni 1 / 4 Mn 3 / 4 CO3 and lithium carbonate are uniformly mixed; the molar ratio of lithium ions in the lithium carbonate to the total metal ions in the precursor is 1.2; (2) The powders after uniform mixing in step (1) are spread on a carbon cloth and calcined in air. The current is 50A and the target temperature is 950°C. After reaching the target temperature, the temperature is maintained for 20 seconds. In the air environment, the heating and cooling speed is about 400°C / s. Finally, the lithium-rich manganese-based positive electrode material Li is calcined. 0.96 Ni 0.2 Mn 0.6 O2.
[0028] Example 5 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-deficient" layered spinel composite phase by a rapid thermal shock method. The preparation method is the same as that of Example 1 except that the molar ratio of lithium ions in the lithium carbonate lithium salt to the total metal ions in the precursor is 1.3 in step (1). Finally, the lithium-rich manganese-based positive electrode material Li 1.04 Ni 0.2 Mn 0.6 O2.
[0029] Example 6 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-deficient" layered spinel composite phase by a rapid thermal shock method. The preparation method is the same as that of Example 1 except that the molar ratio of lithium ions in the lithium carbonate lithium salt to the total metal ions in the precursor is 1.4 in step (1). Finally, the lithium-rich manganese-based positive electrode material Li 1.12 Ni 0.2 Mn 0.6 O2.
[0030] Example 7 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-defective" layered spinel composite phase by a rapid thermal shock method. The preparation method is the same as that of Example 1 except that the power-on time in step (2) is 10 seconds. Finally, the lithium-rich manganese-based positive electrode material Li 0.96 Ni 0.2 Mn 0.6 O2.
[0031] Example 8 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-deficient" layered spinel composite phase by a rapid thermal shock method. The preparation method is the same as that of Example 1 except that the power-on time in step (2) is 40 seconds. Finally, the lithium-rich manganese-based positive electrode material Li 0.96 Ni 0.2 Mn 0.6 O2.
[0032] pass Figure 4 Layered spinel composite structure lithium-rich manganese-based cathode materials with different lithium deficiency prepared by high temperature thermal shock method x Ni 0.2 Mn 0.6 As can be seen from the first cycle charge and discharge curve of the O2 sample as an electrode material at a current density of 0.1C, Li 1.12 Ni 0.2 Mn 0.6 O2、Li 1.04 Ni 0.2 Mn 0.6 O2、Li 0.96 Ni 0.2 Mn 0.6 O2、Li 0.88 Ni 0.2 Mn 0.6 The first cycle discharge specific capacities of O2 materials at 0.1 C are 266, 266, 282, and 277 mAh g −1 , the coulombic efficiencies were 75.6%, 75.6%, 94%, and 90.9%, respectively. When the molar ratio of lithium ions in lithium carbonate to the total metal ions in the precursor is 1.1 (Li 0.88 Ni 0.2 Mn 0.6 O2 material), although the lithium deficiency has reached 26%, the rapid temperature rise and fall and extremely short insulation time caused by high-temperature thermal shock prompt the rapid embedding of lithium ions in the lithium-deficient lithium-rich manganese-based positive electrode material to form a positive electrode material with uniform element distribution, which inhibits the phase separation of lithium-rich and manganese-rich phases under extreme lithium deficiency, so that the first-cycle discharge capacity and the first coulombic efficiency can also be maintained at a very high performance level. The hollow 16c sites in the lithium vacancy spinel phase produced by a large amount of lithium deficiency can store more lithium ions, reduce the irreversible loss capacity of the first cycle, and thus improve the discharge specific capacity and coulombic efficiency. However, compared with the molar ratio of 1.2 (Li 0.96 Ni 0.2 Mn 0.6 O2 material), Li 0.88 Ni 0.2 Mn 0.6 O2 material contains the most spinel phase. Figure 5The mid-cycle curve shows that the cycle performance is inferior to Li 0.96 Ni 0.2 Mn 0.6 O2 material.
[0033] Figure 5 The cycling performance of lithium-rich materials with different lithium contents at 1 C shows that Li 1.12 Ni 0.2 Mn 0.6 O2、Li 1.04 Ni 0.2 Mn 0.6 O2、Li 0.96 Ni 0.2 Mn 0.6 O2、Li 0.88 Ni 0.2 Mn 0.6 The reversible capacities of the O2 materials after 200 cycles at 1C were 143, 134, 176, and 155 mAh g, respectively. −1 , the capacity retention rates are 68.9%, 66.3%, 80% and 75% respectively. 0.96 Ni 0.2 Mn 0.6 O2 material has the highest capacity retention rate (80%), which is related to the good crystal structure, appropriate grain size and moderate spinel phase content of the material.
[0034] Comparative Example 1 This comparative example provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-deficient" layered spinel composite phase by a rapid thermal shock method. The preparation method is the same as Example 1 except that the molar ratio of lithium ions in the lithium carbonate lithium salt to the total metal ions in the precursor is 1.5. Finally, the lithium-rich manganese-based positive electrode material Li 1.2 Ni 0.2 Mn 0.6 O2.
[0035] Comparative Example 2 This embodiment provides a method for preparing a lithium-rich manganese-based positive electrode material by synthesizing a "lithium-deficient" layered spinel composite phase using a rapid thermal shock method. The preparation method: (1) A lithium-rich manganese-based lithium-containing precursor is synthesized by a sol-gel method. The specific method is as follows: lithium acetate, nickel acetate and manganese acetate are dissolved in anhydrous ethanol according to a stoichiometric ratio to form solution A. Citric acid is dissolved in anhydrous ethanol to form solution B. Anhydrous ethanol is added to a three-necked flask, and the three-necked flask is placed in an oil bath for heating. Solutions A and B are simultaneously added to the three-necked flask at a certain rate, and stirred at a constant speed during the titration process. The heating temperature is 80°C. After the titration is completed, the heating temperature of the oil bath is increased to 100°C until the sol is completely converted into a gel. After gelation, the three-necked flask is placed in a vacuum drying oven for drying for a period of time. The heating temperature is 100°C and the heating time is 12h to obtain a dried lithium-containing lithium-rich manganese-based precursor; the molar ratio of lithium ions in the lithium acetate lithium salt to the total metal ions in the precursor is 1.2.
[0036] (2) The lithium-rich manganese-based lithium-containing precursor powder synthesized by the sol-gel method was spread on a carbon cloth and calcined in air. The current was 45A and the target temperature was 900°C. After reaching the target temperature, it was maintained for 20 seconds. In the air environment, the heating and cooling rates were all about 400°C / s, and finally calcined to form a lithium-rich manganese-based positive electrode material Li 0.96 Ni 0.2 Mn 0.6 O2.
[0037] Figure 4 The comparative material Li 1.2 Ni 0.2 Mn 0.6 The first cycle discharge capacity of O2 at 0.1C is 250 mAh g −1 , and the coulombic efficiency is 61% respectively. When the lithium content is the normal theoretical value, its first coulombic efficiency is only 61%, with a large irreversible capacity, and the capacity retention rate after 200 cycles at 1C is 80.6% ( Figure 5 ).
[0038] Figure 6 The synthesis of lithium-rich manganese-based cathode materials with different lithium deficiencies was demonstrated using a traditional tube furnace with slow heating. x Ni 0.2 Mn 0.6 The first cycle charge and discharge curve of the O2 sample as an electrode material at a current density of 0.1C shows that Li 1.12 Ni 0.2 Mn 0.6 O2、Li 1.04 Ni 0.2 Mn 0.6 O2、Li 0.96 Ni 0.2 Mn 0.6 O2、Li 0.88 Ni 0.2 Mn 0.6The first cycle discharge specific capacities of O2 materials at 0.1C are 266, 252, 183, and 159 mAh g −1 , the coulombic efficiency is 76%, 81%, 88% and 104.8% respectively. It can be seen that as the amount of lithium is reduced, the charge capacity and discharge capacity decrease, and the coulombic efficiency gradually increases. 1.2 Ni 0.2 Mn 0.6 O2 and Li 1.12 Ni 0.2 Mn 0.6 O2 material has the highest reversible capacity retained during the cycle, while Li 1.12 Ni 0.2 Mn 0.6 The first-cycle coulombic efficiency of O2 material is higher than that of Li 1.2 Ni 0.2 Mn 0.6 O2. It can be seen that the maximum lithium deficiency during the tubular furnace calcination process cannot exceed 7%. The lithium content continues to decrease. During the high-temperature and long-term calcination process, the lithium ion embedding is slow. The insufficient lithium content and the slow lithium ion embedding will cause the lithium-rich and manganese-rich phases in the material to separate, which in turn affects the first-cycle reversible capacity. When the lithium deficiency reaches 14% (Li 1.04 Ni 0.2 Mn 0.6 O2 material), the first cycle discharge capacity is only 183 mAh g −1 Therefore, the use of a tube furnace for long-term high-temperature calcination to prepare a lithium-rich manganese-based positive electrode material with a "lithium-deficient" layered spinel composite phase requires an appropriate amount of lithium. Too little lithium will cause structural collapse, which in turn affects the capacity. At the same time, Figure 7 The XRD patterns of the lithium-rich manganese-based lithium-containing precursor prepared by the sol-gel method after thermal shock heating are shown, showing poor crystallinity and small particles. 0.96 Ni 0.2 Mn 0.6 A weak NiO diffraction peak appeared on the left side of the (104) peak of O2, indicating the generation of impurities. Figure 8 The 0.1C charge-discharge curve of the positive electrode material is shown, and the capacity is low. Therefore, the lithium-rich manganese-based precursor particles prepared by the co-precipitation method have uniform size, and the prepared positive electrode material has excellent performance and strong contrast.
[0039] Table 1 shows the electrochemical properties of lithium-rich manganese-based positive electrode materials with different lithium deficiencies obtained in the examples and comparative examples. The test results are as follows: Table 1 <![CDATA[Initial discharge specific capacity / mAh g −1 > First cycle coulomb efficiency / % 200 cycles retention rate Example 1 282 94 80 Example 2 277 90.9 75 Example 3 272 93 77 Example 4 262 83 75 Example 5 266 75.6 66.3 Example 6 266 76 68.9 Example 7 272 90.7 80 Example 8 267 96 77.2 Comparative Example 1 250 75 80.6 Comparative Example 2 184 87 75 It can be seen from the above table that the lithium deficiency of the lithium-rich manganese-based positive electrode material of the "lithium-deficient" layered spinel composite phase prepared by high-temperature thermal shock can reach 20%, and its electrochemical performance is optimal. The present invention utilizes the rapid temperature rise and fall and extremely short insulation time of high-temperature thermal shock to promote the rapid embedding of lithium ions in the lithium-deficient lithium-rich manganese-based positive electrode material to form a positive electrode material with uniform element distribution, inhibiting the phase separation of lithium-rich and manganese-rich phases under extreme lithium deficiency, so that the first-cycle discharge capacity and the first coulomb efficiency can also be maintained at a very high performance level, which is impossible to achieve with a traditional tubular furnace. This method can greatly reduce the amount of lithium to a great extent, saving the cost of lithium source, and the process steps are simple, which is expected to achieve large-scale promotion and production. At the same time, it provides a design idea for lithium-rich manganese-based positive electrode materials with lithium-deficient layered spinel composite structures.
[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a lithium-deficient layered spinel composite phase lithium-rich manganese-based positive electrode material, characterized in that: The following steps are involved: (1) Ni x Mn 1-x CO3 and lithium salt are mixed; the molar ratio of lithium ions in the lithium salt to total metal ions in the precursor is less than 1.5; 0.2≤x<1; (2) The powders uniformly mixed in step (1) are spread on a heated substrate, and the heated substrate is powered in an air atmosphere to perform a thermal shock treatment on the powders at a temperature of 800-1000° C. for a holding time of 20-60 seconds, thereby obtaining the lithium-deficient lithium-rich manganese-based positive electrode material.
2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of lithium ions in the lithium salt to the total metal ions in the lithium-rich manganese-based precursor is 1.1-1.
4.
3. The preparation method according to claim 1, characterized in that: The molar ratio of lithium ions in the lithium salt to the total metal ions in the lithium-rich manganese-based precursor is 1.
2.
4. The preparation method according to claim 1, characterized in that: The temperature of the thermal shock in step (2) is 900° C. and the duration is 20 seconds.
5. The preparation method according to claim 1, characterized in that: The heating and cooling rate of the thermal shock in step (2) is 100°C / s-500°C / s.
6. The preparation method according to claim 1, characterized in that: The lithium salt in step (1) includes lithium carbonate and / or lithium hydroxide.
7. The preparation method according to claim 1, characterized in that: The heating substrate used in step (2) is carbon cloth, graphite paper, or metal foil.
8. Use of the lithium-deficient layered spinel composite phase lithium-rich manganese-based positive electrode material prepared by the preparation method according to any one of claims 1 to 7 as a positive electrode material for a lithium battery.
Citation Information
Patent Citations
Lithium-defect lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
CN117637994A
Preparation method for synthesizing lithium-rich manganese-based positive electrode material by short-time rapid thermal shock method and application of lithium-rich manganese-based positive electrode material
CN113511692A
Cathode materials for use in lithium cells and batteries
US20230282820A1
A new doping strategy for layered oxide electrode materials used in lithium-ion batteries
WO2022272139A1
Cited By
Preparation method and application of positive electrode material with optimized surface interface structure
CN120127124A
Preparation method and application of positive electrode material surface interface structure optimization
CN120127124B
Lithium-poor high-capacity manganese-based positive electrode material as well as preparation method and application thereof
CN120164929A
Modified nickel cobalt lithium manganate positive electrode material and preparation method thereof, positive electrode plate and lithium ion battery
CN120767324A
Method for regulating and controlling defects of lithium-rich manganese oxide positive electrode material and application
CN122619693A
